2016
DOI: 10.1542/hpeds.2015-0144
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in Hospitalized Children: A Responsibility and Opportunity for Pediatric Hospitalists

Abstract: Poor nutrition is an underrecognized cause of significant morbidity in hospitalized children. 1,2 In addition to presenting with poor nutrition at the time of admission, children often suffer worsening of their nutritional status during the course of a hospitalization, 3,4 often due to providers' underrecognition of ongoing poor intake (see Fig 1). Pediatric hospitalists can and should play a central role in recognizing and treating this common comorbid condition. In this article we highlight the important iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
1
17
1
2
Order By: Relevance
“…This may have to do with a period of rapid growth seen in patients ,2 years old when malnutrition may be more detrimental. 5,7 The model also identified known risk factors for readmission, such as LOS, acute and/or emergent admission, comorbidities, and ED visits, with effect sizes comparable to those found in other studies. 32 The prevalence of malnutrition in 4.7% of the sample of patients in this study is lower than most reported estimates, [8][9][10] but such comparisons are difficult because of differences in how malnutrition may be assessed across different institutions.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This may have to do with a period of rapid growth seen in patients ,2 years old when malnutrition may be more detrimental. 5,7 The model also identified known risk factors for readmission, such as LOS, acute and/or emergent admission, comorbidities, and ED visits, with effect sizes comparable to those found in other studies. 32 The prevalence of malnutrition in 4.7% of the sample of patients in this study is lower than most reported estimates, [8][9][10] but such comparisons are difficult because of differences in how malnutrition may be assessed across different institutions.…”
Section: Discussionsupporting
confidence: 69%
“…6 Worldwide, the prevalence of pediatric malnutrition of hospitalized patients in developed countries has been estimated at 5% to 27%, depending on the criteria used. [7][8][9][10] On the other hand, there has been an abundance of reports over the last several years in regard to pediatric readmissions, their prevalence, causes, metrics, and preventability. [11][12][13][14][15] Malnutrition has not been specifically addressed as a factor in any of the reports.…”
mentioning
confidence: 99%
“…Prevalence of malnutrition ranges from 6% to 41% in Europe, the USA, and Australia and from 8% to 26% in Spain . Malnutrition leads to an increase in infectious complications, length of hospital stay, and weight loss as well as nutrition support needs . Moreover, malnutrition is associated with higher hospital expenses .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, malnutrition is associated with higher hospital expenses . Early detection, especially on admission, leads to an appropriate assessment and a nutrition intervention in order to prevent further decline . Therefore, in recent years, many pediatric nutrition screening tools have been developed .…”
Section: Introductionmentioning
confidence: 99%
“…Nos últimos anos, diversos estudos científicos demonstraram as repercussões da subnutrição hospitalar como co-responsável pela piora da morbidade/mortalidade, má cicatrização de feridas, maior tempo de permanência na ventilação mecânica, prolongamento do tempo de internação, menor rotatividade de leitos, principalmente na (UTI), e maior custo para o tratamento em todo o sistema de saúde (Sahu et al, 2016;Shaughnessy;Kirkland, 2016;Cao et al, 2014;Yeh et al, 2016;Ghorabi et al, 2016).…”
Section: Subnutrição Hospitalarunclassified